Humic substances and modes of application in the rooting of semihardwood cuttings of two olive cultivars - Ritter, Giovana; Villa, Fabíola; Silva, Daniel Fernandes da; Eberling, Tatiane; Guimarães, Vandeir Francisco; Silva, Edvan Costa da; Dória, Joyce (Comunicata Scientiae, 2023)
The objective of this work was to evaluate the rooting of semi - hardwood cuttings of olive trees using humic substances and their application form. Two experiments were conducted under conditions of screen with 30% retention of the radiation and in masonry bed, complete with sand. A low tunnel was built on the site, measuring 5 x 0.80 m and 0.55 m high, covered with transparent tarpaulin, and within the tunnel was an irrigation system such as intermittent misting. The first experiment was the rooting of cuttings of the cultivars Maria da Fé and Ascolano. The experimental design was randomized blocks, in a 2 x 5 factorial scheme. The second experiment consisted in the rooting of the two cultivars by means of three application forms of the commercial product SoloHumics® plus the control. The experimental design was randomized blocks in a 2 x 4 factorial scheme. Data were collected 75 days after assembly and some phytotechnical evaluations were performed. The cuttings of the cultivar Ascolano 315 presented the best rooting in the treatment with humic acids. The commercial product favored a greater average length of the highest root for the Maria da Fé cultivar and the fulvic acids favored Ascolano 315. The best method of application of humic substances occurred in the form of bed irrigation for the cultivar Maria da Fé.